THE IMPLEMENTATION OF MARKETING PUBLIC RELATIONS (MPR) AT 102BESNEAKERS - Sugiar, Dadan; Saragih, Nurhayani (Universitas Mercu Buana, 2025)
This research aims to analyze the implementation of Marketing Public Relations (MPR) carried out by 102besneakers. The concept used is Marketing Public Relations (MPR) which was introduced by Thomas L. Haris in Rohmah (2018) with three strategies, namely Pull Strategy, Push Strategy and Pass Strategy. The results of this study show that the Pull Strategy carried out is to visualize products, provide rare products, conduct flash sale discount programs on Tokopedia and cross-off prices on Shopee and there is a 10 X Money Back guarantee guarantee if the goods offered prove to be non-original. Then the Push Strategy is to offer shoe products with well-known brands, establish good relationships with suppliers, participate in crowded events such as Car Free Day (CFD) as well as advertising in accordance with the focus of the orientation to be achieved and the Pass Strategy carried out is to build good relationships with customers, do social services for orphans and there are plans to sponsor certain communities such as fun football